Study of Corona Discharge Treatment on Physical and Chemical Properties of Cotton Fabric - Nourbakhsh, Shirin; Talebian, Aazam; Valipour, Peiman; Ghaffar Ebadi, Abdol (Asian Journal of Chemistry, 2010)
In this study, cotton fabric was treated by corona discharge under different powers and number of passages. Corona treated cotton was dyed with direct and reactive dyes. pH and wettability of samples were measured and surface morphology of cotton fabric was determined by SEM and FTIR/ATR analysis. Results indicate that corona treatment causes some cracks on the surface of cotton cuticle layer and water can penetrate rapidly into the cotton structure. FTIR/ATR analysis shows when the power and the passages of corona treatment increase the carboxylic acid groups are created. This result is in agreement with pH results that acidification occurs on the surface of cotton.